2021
DOI: 10.1002/ange.202106984
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the N≡N Triple Bond and Unpredicted Formation of the Cyclic 1,3‐Diaza‐2,4‐Diborete (FB)2N2 from N2 and Fluoroborylene BF

Abstract: Ac omplete cleavage of the triple bond of N 2 by fluoroborylene (:BF) was achieved in al ow-temperature N 2 matrix by the formation of the four-membered heterocycle FB(m-N) 2 BF,w hich lacks at rans-annular N À Nb ond. Additionally,t he linear complex FB = N À N = BF and cyclic FB(h 2 -N 2 )w ere formed. These novel species were characterized by their matrix infrared spectra and quantum-chemical calculations.The puckered four-membered-ring B 2 N 2 complex shows ad elocalized aromatic two-electron p-system in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Apparently, the first three bands (1648.3, 1524.0 and 1495.4 cm −1 ) with quite small 11 B shifts (0.4, 1.1 and 1.5 cm −1 ) belong to the C−C stretching vibrations. The 1389.3 cm −1 band, showing a very large boron isotopic shift (33.7 cm −1 ) is the characteristic stretching vibration of the BF moiety in C 6 F 5 BF, which is red‐shifted comparing to those of 10 BF (1412.2 cm −1 , N 2 ‐matrix) [24] and FBTiF 2 (1404 cm −1 , Ar‐matrix) [25] . The bands at 939.4 and 623.3 cm −1 show large isotopic shifts (9.5 and 9.2 cm −1 ), indicating that these absorptions can be mainly assigned to the B−C deformation modes.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the first three bands (1648.3, 1524.0 and 1495.4 cm −1 ) with quite small 11 B shifts (0.4, 1.1 and 1.5 cm −1 ) belong to the C−C stretching vibrations. The 1389.3 cm −1 band, showing a very large boron isotopic shift (33.7 cm −1 ) is the characteristic stretching vibration of the BF moiety in C 6 F 5 BF, which is red‐shifted comparing to those of 10 BF (1412.2 cm −1 , N 2 ‐matrix) [24] and FBTiF 2 (1404 cm −1 , Ar‐matrix) [25] . The bands at 939.4 and 623.3 cm −1 show large isotopic shifts (9.5 and 9.2 cm −1 ), indicating that these absorptions can be mainly assigned to the B−C deformation modes.…”
Section: Resultsmentioning
confidence: 99%
“…16 Very recently, Riedel, Wang and co-workers achieved the cleavage of the triple bond in N 2 by fluoroborylene (:BF) in a low- temperature N 2 matrix via the formation of two novel cyclic fluorodiazaborirines and a linear isomer. 17 Also, Eunsung Lee and co-workers reported that the anionic aminocarbene radical can decrease the activation barrier of aminocarbene in a reaction with N 2 . 18 Frustrated Lewis pair (FLP) chemistry has been widely utilized in the activation of a growing range of small molecules, such as H 2 , CO 2 , SO 2 , olefins, CO and so on.…”
Section: Introductionmentioning
confidence: 99%